ON THE STABILITY OF SOLUTIONS FOR THE SEMI-AFFINE VARIATIONAL INEQUALITIES IN HILBERT SPACES - Vũ, Văn Đồng (SCIENTIFIC JOURNAL OF TAN TRAO UNIVERSITY, 2023)
This paper investigates the stability of solutions for the class of semi-affine variational inequalities in real Hilbert spaces whose feasible set does not depend on parametric. As an ap- plication, we obtain the stability of solutions for the paramet- ric quadratically constrained quadratic programming prob- lems in real Hilbert spaces.